Multiproxy Analyses of Stratigraphy and Palaeoenvironment of the Late Palaeolithic Grabow Floodplain Site, Northern Germany. Issue 1 (7th December 2012) - Tolksdorf, Johann Friedrich; Turner, Falko; Kaiser, Knut; Eckmeier, Eileen; Stahlschmidt, Mareike; Housley, Rupert A.; Breest, Klaus; Veil, Stephan
<x xml:space="preserve">Abstract</x> Changing river courses and fluctuations of the water table were some of the most fundamental environmental changes that humans faced during the Late Glacial, particularly as these changes affected areas intensively used for settlement and resource exploitation. Unfortunately, only a few stratigraphies have been documented in the North European plain that show the interaction between river development, vegetation history, and occupation by Late Palaeolithic humans. Here, we present the results of detailed stratigraphical studies (pedology, archaeology, chrono‐, tephra‐, and palynostratigraphy) at the Federmesser site Grabow 15 located in the broad Elbe River valley. The research aimed to produce a model of site formation based on a multiproxy approach, relating the local evidence to the palaeoenvironmental and settlement history of the wider region. After deposition of fluvial sands during the Late Pleniglacial in a braided setting, the river course developed locally toward a meandering system at the transition from the Older Dryas to the Allerød, while periodic flooding led to the deposition of floodplain sediments during the early Allerød. The floodplain was settled by people of the earliest "Federmessergruppen, " who are believed to have chosen this open floodplain area along the river for collecting and processing amber of local origin. Their artifacts became embedded in the aggrading floodplain sediments. In the late Allerød, floodplain sedimentation ceased and a Fluvisol‐type soil developed, indicating a trend toward geomorphic stability. The Fluvisol was then covered by silty floodplain sediments due to a rising water level during the late Younger Dryas resulting in the cessation of human occupation in the area. Subsequent organic‐rich Late Glacial/Holocene sediments preserved the settlement remains to the present.